Bacillus thuringiensis Cry14A family proteins as novel anthelmintics against gastrointestinal nematode parasites - Hoang, Duy; Flanagan, Kelly; Ding, Qian; Cazeault, Nicholas R.; Li, Hanchen; Díaz-Valerio, Stefani; Rus, Florentina; Darfour, Esther A.; Kass, Elizabeth; Petersson, Katherine H.; Nielsen, Martin K.; Liesegang, Heiko; et al. (PLoS neglected tropical diseases, 2024)
Bacillus thuringiensis crystal (Cry) proteins have been expressed in commercial transgenic crops for nearly 30 years, providing safe and effective control of insect pests and significantly reducing the application of hazardous chemical pesticides. B . thuringiensis crystal proteins have also been shown to target parasitic nematodes, including plant parasitic nematodes. Recently, transgenic soybean crops expressing Cry14Ab have been shown to provide control against the soybean cyst nematode Heterodera glycines , marking the first time a crystal protein is being commercialized in transgenic crops for control of a nematode pest. However, apart from H . glycines and the free-living nematode, Caenorhabditis elegans , the breadth of nematode activity of Cry14Ab, e . g ., against gastrointestinal parasitic nematodes (GINs), has not been reported. Here we study the efficacy of Cry14Ab against a wide range of gastrointestinal nematode parasites (GINs) in vitro and in vivo. We find that Cry14Ab is effective in vitro against the barber’s pole worm Haemonchus contortus larvae, small strongyles cyathostomin larvae, the hookworm Ancylostoma ceylanicum adults, the roundworm Ascaris suum L4 larvae, and the whipworm Trichuris muris adults. In rodents infected with GIN parasites, Cry14Ab is effective as an in vivo anthelmintic against the hookworms A . ceylanicum and N . americanus , against the mouse parasite Heligmosomoides polygyrus bakeri , and against the roundworm A . suum . Cry14Ab also variably reduces the reproduction of the whipworm T . muris in vivo. Using optimized profile Markov Models, we looked for other putative anthelmintic Cry proteins and, within this list, identified a Bt crystal protein, GenBank accession no. MF893203, that we produced and demonstrated intoxicated GINs. This protein, with 90% amino acid identity to Cry14Ab, is active against C . elegans , A . ceylanicum adults, and A . suum L4 larvae in vitro. MF893203 was given the official designation of Cry14Ac. Cry14Ac is also an effective in vivo anthelmintic against A . ceylanicum hookworms in hamsters and intestinal A . suum in mice. Taken together, our results demonstrate that Cry14Ab and Cry14Ac have wide therapeutic utility against GINs.